1982
DOI: 10.1161/01.cir.65.4.756
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of acute myocardial infarct size in man by serum CK-MB measurements.

Abstract: SUMMARY This study was performed to determine the relationship between myocardial infarct size estimated by serum CK-MB methods and the extent of irreversible injury in acute myocardial infarction. In 321 consecutive patients, infarct size was estimated by different mathematical models, and in 22 patients who died in hospital, the extent of myocardial necrosis was determined by autopsy. We also investigated the depletion of CK-MB in infarcted tissue, the recovery of CK-MB in the plasma volume, and the eliminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0
2

Year Published

1983
1983
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(42 citation statements)
references
References 42 publications
4
36
0
2
Order By: Relevance
“…We have earlier shown that the electrophoretic method may be used to estimate infarct size (13). Our data clearly demonstrate that similar results would be obtained with the dry chemistry method.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We have earlier shown that the electrophoretic method may be used to estimate infarct size (13). Our data clearly demonstrate that similar results would be obtained with the dry chemistry method.…”
Section: Discussionsupporting
confidence: 86%
“…Finally the electrophoretic method and dry chemistry method were used to estimate infarct size (13) in eight patients with acute myocardial infarction. Creatine kinase-MB was measured by both methods in 9 -11 serum samples taken from each patient over two days (about every four hours).…”
Section: Estimation Of Infarct Sizementioning
confidence: 99%
“…Until now, the studies on jeopardized myocardium and infarct sizing have primarily used ST deviations and QRS scores [6][7][8]. In fact, biochemical markers, primarily CK-MB and troponin (Tn) T, have long been used for infarct sizing [9][10][11][12][13][14]. In this context, for infarct sizing, markers like CK-MB and myoglobin are more appropriate than Tn T because of the higher rate of rising and falling serum levels.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies also have produced convincing correlations between enzymatic and histologic estimates of infarct size. [4][5][6][7] After permanent coronary occlusion in the dog, however, only about 15% of the total creatine kinase (CK) activity depleted from the heart was recovered in plasma,8 and it was shown that even a limited variability in this recovery would cause large errors in the estimates.9 Such variability was indeed demonstrated. '0411 Moreover, it was reported that this figure of 15% was changed significantly after interventions such as reperfusion12 and lymphatic obstruction.…”
mentioning
confidence: 99%